An unusual combination of extrapulmonary manifestations of tuberculosis in a child - Abdulnasir Al-Otaibi; Maha Almuneef; Tahir Hameed (Elsevier, 2012)
Summary: We report the case of a 10-year-old girl who presented to the emergency department with acute abdominal pain. She was diagnosed as having extrapulmonary tuberculosis (TB) with multifocal osteomyelitis of the spine and ribs, peritonitis and intestinal involvement. We describe the clinical presentation of this unusual constellation of the disease in the absence of pulmonary involvement in a child and discuss the diagnostic challenges and treatment of these rare forms of TB. Keywords: Child, Tuberculosis, Abdominal tuberculosis, Gastrointestinal tuberculosis, Skeletal tuberculosis